Analisis Dampak Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Level I-IV terhadap Pendapatan Pedagang Kaki Lima Merdeka Walk di Kota Medanalisis Sumber Daya Manusia: Sistematisasi Topik dan Arah Penelitian dari Literatur Terpilih - Nuh Aulya Sari Lubis; Reni Ria Armayani; Faizatun Nisa’; Aldy Fernando; Deva Kumala Sari (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
During the COVID-19 pandemic, many had a very large and bad impact on life, especially for traders, both small traders and small traders, not only that, the implementation of community activity restrictions (PPKM) resulted in traders not being allowed to sell during the PPKM level. One of the impacts of the implementation of Community Activity Restrictions (PPKM) is the impact on street vendors around Merdeka Walk (PKL) in the city of Medan. The purpose of this research is to analyze the impact of the implementation of Community Activity Restrictions (PPKM) Levels I-IV on the Income of Merdeka Walk Street Vendors in Medan City, the research method in this study uses a qualitative method with data collection by interview. The results of interviews with street vendors on the income of street vendors around Merdeka Walk Medan. Keywords: PPKM, Income, Street Vendor